pCO2 distribution and CO2 flux on the inner continental shelf of the East China Sea during summer 2011 - 曲宝晓 宋金明 李学刚 袁华茂 李宁 马清霞 (Chinese journal of oceanology and limnology, 2013)
Measurements ofpH, total alkalinity （TA）, partial pressure of CO2 （pCO2） and air-sea CO2 flux （FCO2） were conducted for the inner continental shelf of the East China Sea （ECS） during August 2011. Variations in pCO2 distribution and FCO2 magnitude during the construction of the Three Gorges Dam （TGD） （2003-2009）, and the potential effects of the TGD on the air-sea CO2 exchange were examined. Results showed that the ECS acts as an overall CO2 sink during summer, with pCO2 ranging from 107 to 585 p.atm and an average FCO2 of -6.39 mmol/（m2·d）. Low pCO2 （〈350 μatm） levels were observed at the central shelf （28°-32°N, 123°-125.5°E） where most CO2-absorption occurred. HighpCO2 （〉420 μatm） levels were found in the Changjiang estuary and Hangzhou Bay which acted as the main CO2 source. A negative relationship between pCO2 and salinity （R2=0.722 0） in the estuary zone indicated the predominant effect of the Changjiang Diluted Water （CDW） on the seawater CO2 system, whereas a positive relationship （R2=0.744 8） in the offshore zone revealed the influence of the Taiwan Current Warm Water （TCWW）. Together with the historical data, our results indicated that the CO2 sink has shown a shift southwest while FC02 exhibited dramatic fluctuation during the construction of the TGD, which is located in the middle reaches of the Changjiang. These variations probably reflect fluctuation in the Changjiang runoff, nutrient import, phytoplankton productivity, and sediment input, which are likely to have been caused by the operations of the TGD. Nevertheless, the potential influence of the TGD on the CO2 flux in the ECS is worthy of further study.